Mind over meds [large type] : know when drugs are necessary, when alternatives are better-- and when to let your body heal on its own - Weil, Andrew (Little, Brown and Company, 2017)
Prescription drug use in America has increased tenfold in the past fifty years, and over-the counter drug use has risen just as dramatically. Modern drugs can be miraculously life saving, and many illnesses require their use. But what happens when our reliance on powerful pharmaceuticals blinds us to their risks? Weil alerts readers to the problem of overmedication and outlines when medicine is necessary and when it is not. He provides reliable integrative-medicine approaches to treating common ailments like high blood pressure, allergies, depression, and even the common cold.